극지용 FPSO의 DP 성능에 영향을 미치는 빙 파라미터 분석에 관한 연구 - 최솔미(Sol-Mi Choi); 이승재(Seung-Jae Lee); 한소령(Solyoung Han); 이재용(Jaeyong Lee) (Han-guk haeyang gonghak hoeji (Online), 2018)
Recently, various efforts have been made to develop oil and gas in the Arctic Ocean. It is very important to consider the load caused by ice in designing floating structures in the area. The magnitude of the ice load and its impact on a structure should be considered. In this paper, we analyze ice parameters affecting the DP performance of FPSO with a DP-assisted mooring system. Several ice characteristics are selected, and the resulting ice load is calculated using GEM software. Numerous simulations are conducted while changing the values of the parameters, and DP capability plots are generated to visualize the effects of changing these parameters. It is shown that the ice drift speed and thickness are the major properties to be considered in DP system design. The limitations of the analysis and future work are discussed in the conclusion.